2021
DOI: 10.1371/journal.pone.0241732
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two DNA extraction kits for profiling poultry respiratory microbiota from multiple sample types

Abstract: Characterization of poultry microbiota is becoming increasingly important due to the growing need for microbiome-based interventions to improve poultry health and production performance. However, the lack of standardized protocols for sampling, sample processing, DNA extraction, sequencing, and bioinformatic analysis can hinder data comparison between studies. Here, we investigated how the DNA extraction process affects microbial community compositions and diversity metrics in different chicken respiratory sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…First, the difference in DNA extraction efficiency among different bacteria must be minimized. This condition could be satisfied using the ZymoBIOMICS DNA Miniprep Kit, which has been shown to be an effective extraction method for 16S rRNA amplicon analysis referred in several papers [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the difference in DNA extraction efficiency among different bacteria must be minimized. This condition could be satisfied using the ZymoBIOMICS DNA Miniprep Kit, which has been shown to be an effective extraction method for 16S rRNA amplicon analysis referred in several papers [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result shows that although the separation of skin layers may not be extremely precise, this will have a limited influence on the PCR results. This result may be explained by the fact that modern extraction kits are efficient in isolating different sorts of biological samples ( Manta et al, 2020 ; Abundo et al, 2021 ). Although there is controversy related to blood samples ( Manta et al, 2020 ), previous studies have also not found significant differences in accuracy properties depending on different sample types when evaluating molecular biology techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Our optimized methods for sequencing and sequence processing are detailed in our recent reports ( Abundo et al, 2021 ; Taylor et al, 2020 ). For each sample, DNA was quantified using NanoDrop 2000c spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA), adjusted to a concentration of 100 ng/µL, and shipped to the University of Minnesota Genomics Center (Minneapolis, MN, USA) for sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Avian influenza viruses are among the numerous pathogens that induce strong innate immune responses such as IFNs and pro-inflammatory cytokines ( Akira, Uematsu & Takeuchi, 2006 ; Medzhitov & Janeway Jr, 2000 ; Mogensen, 2009 ) which can trigger dysbiosis in the respiratory tract of mammals ( Duvigneau et al, 2016 ; Engelsoy, Rangel & Demirel, 2019 ; Madouri et al, 2018 ; Sharma-Chawla et al, 2019 ) and in the avian gut ( Ganz et al, 2017 ; Hird et al, 2018 ; Li et al, 2018 ; Yitbarek et al, 2018c ; Zhao et al, 2018 ). However, influenza virus-induced dysbiosis of avian respiratory microbiota has not been described due to challenges in respiratory sampling methodologies ( Abundo et al, 2020 ; Abundo et al, 2021 ). Furthermore, there is a lack of information about the impacts of influenza virus infection on turkey microbiota despite turkeys generally being highly susceptible to diverse influenza virus strains ( Pantin-Jackwood et al, 2017 ; Pillai et al, 2010b ; Tumpey, Kapczynski & Swayne, 2004 ).…”
Section: Introductionmentioning
confidence: 99%